COVID-19 AND THE QUALITY OF AUDIT EVIDENCE: ASSESSING THE IMPACT ON AUDITING PRACTICES IN INDIA - Kiran, Asha; Kaur, Parminder; Geetika; Gupta, Harshita; Rajput, Sakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
COVID-19 pandemic was truly the striking booster for the surgical empowerment of Digital era and marketing. It revolutionized and transformed the B2B to B2C era. Although the awareness of Digital Marketing was buzzing in air before COVID-19, the visibility was certainly low. Few Top-rated brand corporates were progressively alert about its gravity-based largescale markets, big-size revenue, ensured that digital marketing would create a consumer-driven importance in a way ahead of bridging effective communication between consumers and businesses. Remote-and Hybrid working was the ultimatum in bringing more Online Business to the Marketing Managers onboard. The global consumers were highly influenced by trending digital campaigns and contents popped out on popular social digital platforms. Due to insufficient budget, startups were the first-time game changing players in markets who incessantly fought against all odds facing while developing the software on-demand. Extreme programming and Kanban made things possible and finally experts built viable interface for supporting efficient online infra through consumer-friendly apps and websites. The business corpus was entirely into online campaigns and held onto “Everything’s just ONLINE.” The data shows that out of many challenges, during the phase of COVID-19, 59% of some listed companies fueled their efforts on solving problems in areas of digital marketing and 66% of them finished of the task waiting for an ONLINE world that never was before. POST-COVID was full of new wave excitement, unlimited opportunities piled up for skilled digital marketers and service providers. The hiring process of these skilled content creators, digital marketing managers and online advertisers was just a culture shock in the new age digital era, however, “everything’s just Online” is the outstanding local to global trend in continuing.